2014
DOI: 10.1063/1.4880118
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the solid-state charge mobility in a model radical polymer

Abstract: We establish that an oft-used radical polymer, poly(2,2,6,6-tetramethylpiperidinyloxy methacrylate) (PTMA), has a solid-state hole mobility value on the order of 10−4 cm2 V−1 s−1 in a space charge-limited device geometry. Despite being completely amorphous and lacking any π-conjugation, these results demonstrate that the hole mobility of PTMA is comparable to many well-studied conjugated polymers [e.g., poly(3-hexylthiophene)]. Furthermore, we show that the space charge-limited charge carrier mobility of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Therefore, electrolyte‐supported radical polymer systems have extremely useful transport properties, as the liquid‐based electrolytes provide ample mobility to the radical polymer pendant groups. On the other hand, only recently was it established that these types of reactions can also occur in a rather rapid manner in solid‐state organic electronic applications . Specifically, the model radical polymer, poly(2,2,6,6‐tetramethylpiperidinyloxy methacrylate) (PTMA), is an extraordinarily transparent material and can be easily synthesized in large batches .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, electrolyte‐supported radical polymer systems have extremely useful transport properties, as the liquid‐based electrolytes provide ample mobility to the radical polymer pendant groups. On the other hand, only recently was it established that these types of reactions can also occur in a rather rapid manner in solid‐state organic electronic applications . Specifically, the model radical polymer, poly(2,2,6,6‐tetramethylpiperidinyloxy methacrylate) (PTMA), is an extraordinarily transparent material and can be easily synthesized in large batches .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a PTMA-co-PVS macromolecule containing 12% PVS (on a molar basis) was sandwiched between ITO and Al contacts to form the ITO/PTMA-co-PVS/Al space charge-limited device geometry. Previously, we have demonstrated that the singularly occupied molecular orbital (SOMO) energy level that is used to transport charge in PTMA forms a nearly ohmic contact with ITO and that the work function of Al is so far-removed from this transport level that the Al contact serves as an excellent blocking electrode [27]. Because the hole and electron diffusion are negligible in this system and the hole mobility is fieldindependent over the voltages employed, there is a region of the current density versus voltage curve that can be modeled according to the Mott-Gurney relationship (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric constant was assumed to be 3.4 because this is the experimentally-measured dielectric constant of PTMA, and representative current voltage versus voltage curves are depicted in Fig. 7a [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical polymers (i.e., macromolecules with nonconjugated backbones but with stable radical sites attached as pendant groups on the polymer chain) have emerged as potentially revolutionary materials in a host of organic electronic devices; [26][27][28][29][30][31] however, they have not been utilized as charge-conducting layers in OPV devices. Here we fundamentally alter this archetype, and we demonstrate that the addition of a PTMA layer, which can be deposited from solution, causes these inverted OPV devices to have a reproducible open-circuit voltage (V oc ) of 0.6 V. Additionally, the V oc does not vary with respect to device exposure to ambient conditions over the course of multiple days, even when the easilyoxidized thin film of silver (Ag) is used as the anodic contact.…”
mentioning
confidence: 99%